3D Room Visualization on Android Based Mobile Device (with Philips™’ Surround Sound Music Player) - Durio Etgar; Wahyul Amien Syafei; Jack Zijlmans; Zhaorui Yuan (International Journal of Science and Engineering, 2013)
This project’s specifically purposed as a demo application, so anyone can get the experience of a surround audio room without having to physically involved to it, with a main idea of generating a 3D surround sound room scenery coupled with surround sound in a handier package, namely, a “Virtual Listen Room”. Virtual Listen Room set a foundation of an innovative visualization that later will be developed and released as one of way of portable advertisement. This application was built inside of Android environment. Android device had been chosen as the implementation target, since it leaves massive development spaces and mostly contains essential components needed on this project, including graphic processor unit (GPU).  Graphic manipulation can be done using an embedded programming interface called OpenGL ES, which is planted in all Android devices generally. Further, Android has a Accelerometer Sensor that is needed to be coupled with scene to produce a dynamic movement of the camera. Surround sound effect can be reached with a decoder from Phillips called MPEG Surround Sound Decoder. To sum the whole project, we got an application with sensor-dynamic 3D room visualization coupled with Philips’ Surround Sound Music Player. We can manipulate several room’s properties; Subwoofer location, Room light, and how many speakers inside it, the application itself works well despite facing several performance problems before, later to be solved. [Keywords : Android,Visualization,Open GL; ES; 3D; Surround Sensor]